Sosialisasi Identitas Kependudukan Digital Dalam Meningkatkan Kesadaran Kepemilikan Administrasi Kependudukan di Desa Kaima Kecamatan Kauditan Minahasa Utara - Ferdinandus Jaftoran; Djouhari Kansil; Piet Hein Pusung; Suraji; Arnold F. Bura; Achfrilia Anggie Sumampouw; Secilia Toheba; Ni Putu Vanya Visvanitra; Andika Jonathan Watung; Sigit Wirayudha (Civitas Consecratio: Journal of Community Service and Empowerment, 2025)
Kaima village government data shows that 75% of Kaima village residents prefer to manage agriculture and plantations as their source of income and family finances, and they lack the time to process population documents. Kaima Village officials provide door-to-door service to complete population documents for Kaima residents. The purpose of this community service activity is to increase the knowledge of Kaima Village residents regarding digital-based population administration services and to provide assistance, along with village officials, in the process of obtaining mandatory population documents. The introduction of Digital Population Identity (IKD) is expected to facilitate the community in meeting population administration needs, while for the village government, it serves as a crucial tool for data validation that supports development planning, economic growth, and human resource development. This community service activity is implemented through outreach, Focus Group Discussions (FGDs), training, and special assistance for the elderly and people with disabilities. The method used is ODSIMED (Observation, Development, Socialization, Implementation, Monitoring, and Dissemination).This outreach activity was attended by both community members and village officials, with speakers from the North Sulawesi Provincial Population and Civil Registration Office. The material provided covered the use of smartphones for the IKD application, data input procedures, and an introduction to available features. Evaluation results showed a significant increase in participants' knowledge, skills, and awareness regarding the benefits of the IKD. Discussions and questions and answers also demonstrated community enthusiasm for re-applying previously neglected population documents. Thus, this community service activity demonstrated the effectiveness of IKD outreach in raising awareness of population administration ownership while supporting more modern and inclusive village administration.